â€œServices Anthroposphere: Describing Services into Retailing with the Aid of Geosciencesâ€ - Kollias, Odyssefs (European Scientific Journal, ESJ, 2018)
The aim of this conceptual paper is to highlight the importance of senses, emotions and sentiments which create the climate at a commercial venue. Services Anthroposphere is a new interdisciplinary concept and terminology employed in the provision of services. The term â€œAnthroposphereâ€ was adopted from Geosciences by combining its meanings with the vital role of atmospherics and that of human action. By broadening this term, new ideas that inspire people to follow are arising. Terminologies help in creating short path in understanding meanings in vocational training. Interdisciplinary terms provide a broader perspective of the concept. Result is the enrichment of communication.